Hsp70- and Hsp90-mediated regulation of the conformation of p53 DNA binding domain and p53 cancer variants - Boysen, Marta; Kityk, Roman; Mayer, Matthias P. (Molecular cell, 2019)
Summary - The activity of the tumor suppressor p53 has to be timed and balanced closely to prevent untimely induction of cell death. The stability of p53 depends on the ubiquitin ligase Mdm2 but also on Hsp70 and Hsp90 chaperones that interact with its DNA binding domain (DBD). Using hydrogen exchange mass spectrometry and biochemical methods, we analyzed conformational states of wild-type p53-DBD at physiological temperatures and conformational perturbations in three frequent p53 cancer mutants. We demonstrate that the Hsp70/Hdj1 system shifts the conformational equilibrium of p53 toward a flexible, more mutant-like, DNA binding inactive state by binding to the DNA binding loop. The analyzed cancer mutants are likewise destabilized by interaction with the Hsp70/Hdj1 system. In contrast, Hsp90 protects the DBD of p53 wild-type and mutant proteins from unfolding. We propose that the Hsp70 and Hsp90 chaperone systems assume complementary functions to optimally balance conformational plasticity with conformational stability.
The article ends with page 843.e4
Gesehen am 26.06.2019